The leadership challenge - Kouzes, James M., 1945-; Posner, Barry Z. (San Francisco, CA : Jossey-Bass, 2007)
The most trusted resource on becoming a leader is now updated and revised for a new generation. This leadership classic continues to be a bestseller after three editions and twenty years in print. It is the gold standard for research-based leadership, and the premier resource on becoming a leader. This new edition, with streamlined text, more international and business examples, and a graphic redesign, is more readable and accessible than ever before. The Leadership Challenge, Fourth Edition, has been extensively updated with the latest research and case studies, and offers inspiring new stories of real people achieving extraordinary results. The authors' central theme remains the same and is more relevant today than ever: "Leadership is Everyones Business." Their "five practices" and "ten commitments" have been proven by hundreds of thousands of dedicated, successful leaders. This edition, with almost one-third new material, emphasizes the global community and refocuses on business leaders.
[pt]. 4. Challenge the process -- 7. Search for opportunities -- Seize the initiative -- Exercise outsight -- Reflection and action -- 8. Experiment and take risks -- Generate small wins -- Learn from experience -- Reflection and action -- 5. Enable others to act -- 9. Foster collaboration -- Create a climate of trust -- Facilitate relationships -- Reflection and action -- 10. Strengthen others -- Enhance self-determination -- Develop competence and confidence -- Reflection and action -- [pt]. 6. Encourage the heart -- 11. Recognize contributions -- Expect the best -- Personalize recognition -- Reflection and action -- 12. Celebrate the values and victories -- Create a spirit of community -- Be personally involved -- Reflection and action -- [pt]. 7. Leadership for everyone -- 13. Leadership is everyone's business -- You are the most important leader in your organization -- Leadership is learned -- Leaders make a difference -- First lead yourself -- Moral leadership calls us to higher purposes -- Humility is the antidote to hubris -- Leadership is in the moment -- The secret to success in life -- Notes -- Acknowledgments -- About the authors -- Index.
Includes bibliographical references (p. 352-368) and index.
Keywords: Leadership; Executive ability; Management; Leadership; Administrative Personnel; Organization and Administration; Personnel Management; Efficiency, Organizational; Leadership